Populist narratives, digital media, and public perceptions of election fraud in the Indonesian presidential elections 2019 and 2024 - Ferdinand Eskol Tiar Sirait; Irwansyah Irwansyah; Eriyanto Eriyanto (Otoritas : Jurnal Ilmu Pemerintahan, 2026)
Persistent allegations of electoral fraud after Indonesia’s 2019 and 2024 elections show that legitimacy is shaped not only by legal validation but also by competing public narratives. Although both elections were certified, post-election discourse remained marked by polarization, distrust, and manipulation claims. Existing studies have examined fraud perceptions, populism, misinformation, and digital politics separately, yet research on how fraud narratives evolved across consecutive Indonesian elections remains limited. This study addresses this gap by analyzing how populist fraud narratives were produced and circulated in both elections, and how survey institutions contributed to electoral legitimacy. Using qualitative descriptive content analysis based on library and document-based research, this study synthesizes academic literature, official documents, media reports, and survey publications. The findings reveal a transformation in fraud narratives. In 2019, they were explicit, personalized, and elite-centered, articulated by senior political and religious actors, and linked to offline mobilization. In 2024, they became decentralized, implicit, and digitally networked, circulating through short-form content, partisan online communities, and buzzer-like amplification. Across both elections, survey institutions functioned as epistemic actors by measuring public perceptions and countering claims of widespread illegitimacy, while exposing partisan asymmetries and winner’s bias. This article contributes to debates on digital populism, electoral integrity, and democratic legitimacy by showing how election legitimacy is contested across legal-institutional, moral-populist, and empirical-survey arenas.